A graphic tool to help consumers determine when to replace a toothbrush: a cohort study - Muller-Bolla, Michèle; Repetto, Alexandra; Velly, Ana Miriam (International dental journal, 2012)
Objectives: The aim of this study was to create and validate a drawing to help adults establish when to replace a manual toothbrush. Methods: This cohort study had two phases. Phase I (3 months, 50 subjects) aimed to create a drawing of average wear in a toothbrush based on a wear index (WI) of 68% for the tested toothbrush. This was validated in Phase II (3 months, 30 participants). Pictures of worn brushing surfaces were generated using an image acquisition system. Images in each study phase were superimposed to provide a single reference outline to indicate when a toothbrush should be replaced. Residual plaque index values for identical brushing protocols were recorded using new and worn toothbrushes in Phase I and compared using Student’s paired t-test. Student’s t-test was used to compare duration of tooth-brushing and WI values in both phases. Results: After brushing according to a uniform protocol, the residual plaque index at baseline was significantly lower than that at the last use of the toothbrush (P < 0.01). The drawings generated in Phases I and II were similar in terms of WI (P = 0.33) and period of use (P = 0.12). Conclusions: This simple drawing may help adults establish when they should replace a toothbrush.